2011
DOI: 10.1260/1369-4332.14.3.499
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response of Adjacent Steel Structures Connected by Passive Device

Abstract: In this study, the seismic response of adjacent steel structures linked to one another at different floor levels by passive devices is evaluated. Two types of connectors are considered: linear viscous dampers and linear springs. Various combinations of type and location of the connectors are analyzed for wide ranges of their characteristics. Influence of the structural properties (ratio of number of stories and ratio of fundamental periods) and the properties of the excitation (frequency) on the story response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Many experimental and analytical studies have proven that the introduction of damping devices between adjacent buildings provides an efficient mean for improving the seismic performance of the two systems. The behavior of adjacent structures linked by rigid, active, or passive control devices (Soong and Spencer, 2002;Christopoulos and Filiatrault, 2006;Takewaki, 2009) has been object of study of many papers in the last decades Ni et al, 2001;Kim et al, 2006;Cimellaro and Lopez-Garcia, 2007;Roh et al, 2011;Richardson and Walsh, 2012;Tubaldi et al, 2014;Tubaldi, 2015). These studies have shown that the interaction between two systems with different dynamic properties through the connecting devices allows to reduce the structural seismic responses in terms of displacements and accelerations with respect to the unconnected case.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and analytical studies have proven that the introduction of damping devices between adjacent buildings provides an efficient mean for improving the seismic performance of the two systems. The behavior of adjacent structures linked by rigid, active, or passive control devices (Soong and Spencer, 2002;Christopoulos and Filiatrault, 2006;Takewaki, 2009) has been object of study of many papers in the last decades Ni et al, 2001;Kim et al, 2006;Cimellaro and Lopez-Garcia, 2007;Roh et al, 2011;Richardson and Walsh, 2012;Tubaldi et al, 2014;Tubaldi, 2015). These studies have shown that the interaction between two systems with different dynamic properties through the connecting devices allows to reduce the structural seismic responses in terms of displacements and accelerations with respect to the unconnected case.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia [19][20][21][22] have focused deeply on separation distance and suggested some parameters to prevent pounding between structures. Kasai and Maison [23] proposed the spectral difference method based on random vibration theory that considers the first mode approximation for displacements of elastic multi-storey buildings.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the building configuration and damper location on the overall system performance, considering passive and active coupled building control for flexible adjacent buildings modeled as cantilevered beams using the Galerkin method, had been investigated (Christenson et al 2006). The seismic response of adjacent steel structures connected by passive devices (linked by linear viscous dampers and linear springs) are analyzed; the influence of structural properties and properties of the excitation on the responses have been investigated, and the results show that connecting adjacent structure by viscous damper is effective for response control of the structures (Roh et al 2011). The effectiveness of passive damper for response control of dynamically well-separated adjacent coupled structures has been confirmed by above studies.…”
Section: Introductionmentioning
confidence: 99%